Efecto de la aplicación de diferentes niveles de cafeína sobre las características espermáticas en el semen crioconservado de carneros de pelo - Pilamunga Llagua, Erika Belen (2025)
The Ecuadorian sheep industry is thriving thanks to advances in biotechnology, particularly cryopreservation techniques that help maintain semen viability over extended periods and improve the quality of sheep livestock. The objective of the present study was to evaluate the effect of applying different levels of caffeine to the cryopreservation medium on post-thaw sperm characteristics in hair sheep ram semen. The results of the applied treatments were analyzed using a multivariate design with the MANOVA test in SPSS version 26. Semen from two Katahdin hair sheep rams was analyzed. A preservation extender (Triladyl®) was used, and an antioxidant—anhydrous caffeine—was added at three different concentrations across three treatments (T1 = 1 mg caffeine, T2 = 2 mg caffeine, T3 = 3 mg caffeine) compared to a control treatment (T0). Twelve straws per treatment were evaluated through three semen collections, one per animal each week. At the end of the experiment, no significant differences were observed in the macro- and microscopic characteristics of the semen before applying the caffeine levels to the preservation extender (Triladyl®). However, significant differences were found in the microscopic characteristics of the semen after cryopreservation when different levels of caffeine were added to the media. Treatment 2 showed the best performance in both individual motility and post-thaw sperm viability. Finally, a negative correlation was determined between the variables: individual motility and sperm viability versus the treatments, as higher doses of caffeine resulted in lower individual motility and sperm viability.